1991
DOI: 10.1093/clinchem/37.2.281
|View full text |Cite
|
Sign up to set email alerts
|

Osteocalcin concentrations in plasma prepared with different anticoagulants

Abstract: We investigated the effects on plasma osteocalcin concentrations of different anticoagulants used to collect the blood samples. Plasma osteocalcin concentrations measured by enzyme immunoassay and radioimmunoassay are influenced by the nature of the anticoagulants used. The most significant difference between concentrations found in plasma and serum was seen with oxalate/fluoride anticoagulant, which reduced osteocalcin concentrations to 37.3% of serum values. This is probably related to increased hemolysis wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The samples were thawed immediately before use, and only previously unthawed aliquots were used for the serotonin assay. A previous study from our group (9) has demonstrated the stability of osteocalcin, a relatively unstable protein, (10) under our collection and storage conditions.…”
Section: Sample Collectionmentioning
confidence: 86%
“…The samples were thawed immediately before use, and only previously unthawed aliquots were used for the serotonin assay. A previous study from our group (9) has demonstrated the stability of osteocalcin, a relatively unstable protein, (10) under our collection and storage conditions.…”
Section: Sample Collectionmentioning
confidence: 86%
“…This marker is also relatively unstable; its immunoreactivity reportedly decreases by 50–70% after 6–24 hours at room temperature and 40–80% after 2 weeks at 4℃ 2021. Repeated freezethaw cycles also reduce osteocalcin values 22. Moreover, the restricted times during which blood samples could be acquired introduce the possibility of diurnal variations.…”
Section: Discussionmentioning
confidence: 99%
“…Osteocalcin (OC) was measured using an ELISA ( enzyme-linked immunoabsorbent assay ) kit (DIAsource ImmunoAssays S.A., Belgium) [ 23 , 24 ]; the normal reference range is 5–25 ng/mL, with an intra-assay variation of 3–5% and an inter-assay variation of 3.5–5.6%. C-terminal telopeptide (CTX) was measured using an ELISA kit (Immuno Diagnostic Systems Ltd, United Kingdom) [ 25 ]; the normal reference range for postmenopausal women is 0.142–1.351 ng/mL, with an intra-assay variation of 1.7–3% and inter-assay variation of 3–11%.…”
Section: Methodsmentioning
confidence: 99%